Use It or Lose It: Prudently Using Case Study as a Research and Educational Strategy - Shoaib, Shandana; Mujtaba, Bahaudin G. (American Journal of Education and Learning, 2016)
The overarching aim of this paper is to demystify the case study strategy in light of available literature. The paper presents a variety of case study designs for researchers to choose from that fits their research needs. It also seeks to position the case study strategy within the methodological framework of an inquiry that provides guidance to the novice researcher. Moreover, the use of triangulation in a case study strategy has been especially highlighted, followed by what could be the possible analytical techniques for data employed in this type of research. Careful selection of the case study design and the appropriate use of triangulation can enhance the quality of results.